Virtual Jobs: A Quantitative Case Study of Coping with the Stress Level and Identity Crisis - Arya S,; K. Balakrishnan, (International Journal of Psychosocial Rehabilitation, 2020)
Corporate companies across the globe embrace home based work policies to promote employment. With the rapid growth of work from home policies it is very tough to regulate job stress and to motivate the employees. Virtual jobs fail to provide a proper job profile to their employees and fall short in their efficiency to boost their self-esteem. The main objective of this study is to analyse the very term virtual jobs with reference to the factors that influence people to opt for these jobs and its impact on the workers. On the basis of the survey conducted and personal interviews this paper studies the various methods to release stress and how to strike a balance between work and home.